Host life history strategy, species diversity, and habitat influence Trypanosoma cruzi vector infection in Changing landscapes. - Nicole L Gottdenker; Luis Fernando Chaves; José E Calzada; Azael Saldaña; C Ronald Carroll (PLoS Neglected Tropical Diseases, 2012)
Background Anthropogenic land use may influence transmission of multi-host vector-borne pathogens by changing diversity, relative abundance, and community composition of reservoir hosts. These reservoir hosts may have varying competence for vector-borne pathogens depending on species-specific characteristics, such as life history strategy. The objective of this study is to evaluate how anthropogenic land use change influences blood meal species composition and the effects of changing blood meal species composition on the parasite infection rate of the Chagas disease vector Rhodnius pallescens in Panama. Methodology/principal findings R. pallescens vectors (N = 643) were collected in different habitat types across a gradient of anthropogenic disturbance. Blood meal species in DNA extracted from these vectors was identified in 243 (40.3%) vectors by amplification and sequencing of a vertebrate-specific fragment of the 12SrRNA gene, and T. cruzi vector infection was determined by pcr. Vector infection rate was significantly greater in deforested habitats as compared to contiguous forests. Forty-two different species of blood meal were identified in R. pallescens, and species composition of blood meals varied across habitat types. Mammals (88.3%) dominated R. pallescens blood meals. Xenarthrans (sloths and tamanduas) were the most frequently identified species in blood meals across all habitat types. A regression tree analysis indicated that blood meal species diversity, host life history strategy (measured as r(max), the maximum intrinsic rate of population increase), and habitat type (forest fragments and peridomiciliary sites) were important determinants of vector infection with T. cruzi. The mean intrinsic rate of increase and the skewness and variability of r(max) were positively associated with higher vector infection rate at a site. Conclusions/significance In this study, anthropogenic landscape disturbance increased vector infection with T. cruzi, potentially by changing host community structure to favor hosts that are short-lived with high reproductive rates. Study results apply to potential environmental management strategies for Chagas disease.